Bolsonarismo e pós-política: as eleições presidenciais de 2018 sob uma ótica crítica - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The article was conceived as a Course Conclusion Paper (TCC), referring to the Social Work course. Its general objective is to understand the role that depoliticization arising from post-politics played in the establishment of Bolsonarism in the 2018 presidential election, in order to contribute with theoretical and practical subsidies that allow a critical analysis of the Brazilian sociopolitical conjuncture. Aiming to present a counterpoint in mitigating the advances of ultra-reactionary neoliberalism in Brazil and the world. The research was based on qualitative research of exploratory character and was based on the critical dialectic method. The technique used for data collection was documentary research. The sampling employed was the non-probabilistic of the intentional type and the type of data analysis chosen was Critical Discourse Analysis (CDA). Being that the use of post-politics is attenuated from a depoliticized perspective of the Brazilian sociopolitical conjuncture derived from the June 2013 protests in Brazil, its use is permeated with contradictions. The data surveyed highlights the enormous impact of post-politics on the 2018 presidential election. It also encompassed the process of desmocratization of Brazil with the establishment of Bolsonarism starting from the cooptation of Brazilian society by post-politics and depoliticized precepts in the 2018 elections. Furthermore, it was possible to observe how the post-politics continued to draw itself comprehensively in the 2022 election. The results still 4 bring, among several issues, the use of technicality, moralization of corruption and of politics as well as the co-option of the post-political discourse by Brazilian society through the sense of legitimization of the inflammatory discourse of ex-President Jair Messias Bolsonaro and of the fake news spread by him during the 2018 presidential race.
Keywords: Ciência política; Democracia; Eleições - 2018; Análise do discurso; Political Science; Democracy; CNPQ::CIENCIAS SOCIAIS APLICADAS